UNSUR–UNSUR PENDIDIKAN KARAKTER DALAM PAI DAN IMPLIKASINYA TERHADAP SIKAP DAN PERILAKU AGAMA SISWA - Siti Solehah (Jurnal Ilmu Pendidikan dan Sosial, 2022)
Character are psychological, moral, or character traits that distinguish one person from another. Here, character can also be understood as a character or character. Thus, a person with character is a person who has character, has a personality, or has character. Elements of character Attitude, emotion, belief, habit and will, self-conception. The actions, behavior, and attitudes of children today are not something that suddenly appears or is formed or even "given" from the Almighty. There was a long process before which then made these attitudes and behaviors attached to him. In fact, a little or a lot of a child's character has begun to form since he was still a fetus in the womb. There are several values ​​that form a complete character, namely respecting, being creative, having faith, having a scientific basis, synthesizing and doing according to ethics.